The Cultural Transformation of Akkarungeng (A study on Childhood Education Patterns in Bone Regency) - Eka, Eka Paramita (IAIN PAREPARE, 2025)
Background: Akkarungeng culture is a cultural concept containing values that were originally only taught to Bugis aristocrats/Arung. Based on the word Akkarungeng itself, Akkarungeng was an area where an Arung Mangkau' ruled. After undergoing cultural transmission, it turned into a value concept that has become a legacy for all Bugis people to this day and is part of the Pengadereng Culture contained in Lontara Latoa Tana Bone. Research Objectives: This study aims to examine and analyse the pattern of child education applied by parents in Bone Regency while still implementing Akkarungeng cultural values. Methods: This research uses a qualitative approach with descriptive methods, applying observation, in-depth interviews with expert sources, and documentation, as well as the data sources obtained, namely primary data which is the main data used by researchers, while the secondary data used in this research relates to literature reviews that support this research. The data obtained was analysed through triangulation to ensure the validity of the findings. Results: This study found that the Akkarungeng culture consists of four personal values including, ᨒᨛᨇᨘ Le ̂mpu (Honest), ᨁᨛᨈᨛᨂ Ge ̂tte ̂ng (firm/consistent), ᨕᨉ ᨈᨚᨂᨛ Ada Tonge ̂ng (Correct Speech), and ᨈᨛᨆᨄᨔᨗᨒᨕᨗᨂᨛ Te ̂mmappasilainge ̂ng (Not Discriminating) still applied by parents in Bone Regency in educating children through by going through three stages of guiding, directing and coaching. Conclusions: Akkarungeng Cultural Values contain four main values that are applied by parents in Bone Regency, with the presence of this research is expected to provide an understanding to the wider community that the values that are still preserved have undergone transmission and become cultural wisdom that should be known and preserved. Keywords: Akkarungeng Cultural 1; Childhood Education 2; Pengadereng 3